2022 Founder's Lecture: Current Research Trends in Mathematics Learning that Guide Us for the Future. (2nd October 2022) - Wilkerson, Trena L.
ABSTRACT: Mathematics teaching and learning are critical aspects of education that impact our world. There are implications for the mathematics education research community that should push us to have critical conversations about our research and how it informs mathematics education. I present a brief overview of research in mathematics education through the lens of Investigations in Mathematics Learning, the official journal of the Research Council on Mathematics Learning, using issues from 2017-2021. Included are findings from qualitative analyses and ideas calling on the mathematics education community to consider that provide a positioning for mathematics education researchers (MERs). I challenge us to consider multiple questions with regard to our research: What does it add to the field of mathematics education? How does it contribute to broadening and deepening our understandings? How does it inform practice to further effective equitable teaching and learning of mathematics? Are we being inclusive? Are we a leading voice in mathematics education research and are we being effective curators and stewards of this work? As MERs, as a field, as professional organizations, what could and should we do? We have a unique opportunity at this juncture to work together to inform and impact mathematics learning in profound ways.